1996
DOI: 10.1002/(sici)1520-6394(1996)4:6<257::aid-da1>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Onset of antidepressant activity: Reexamining the structure of depression and multiple actions of drugs

Abstract: The question of when antidepressant drugs (AD) initiate significant clinical actions in depressed patients is still unsettled. Findings from early studies on whether there is a lag in the onset of therapeutic actions were in disagreement. More recent results with the selective serotonin reuptake inhibitors (SSRIs) and other new Ads indicate that clinical actions occur within the first 2 weeks. In this paper, evidence from efficacy studies with the Ads is reviewed and the methodologic and conceptual obstacles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…He concluded that the usual response for patients treated with antidepressants appeared to be immediate, "at least immediate in terms of 1 week" and might be attributable to the natural course of the illness. Similar observations have been reported (Coryell et al 1982;Katz et al 1987;Casper et al 1994;Stassen et al 1994;Katz et al 1994). A contrary position, according to which there is at least a delay of several weeks in the onset of true drug effect, has been suggested by others (Quitkin et al 1987).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…He concluded that the usual response for patients treated with antidepressants appeared to be immediate, "at least immediate in terms of 1 week" and might be attributable to the natural course of the illness. Similar observations have been reported (Coryell et al 1982;Katz et al 1987;Casper et al 1994;Stassen et al 1994;Katz et al 1994). A contrary position, according to which there is at least a delay of several weeks in the onset of true drug effect, has been suggested by others (Quitkin et al 1987).…”
supporting
confidence: 80%
“…They suggest that effect sizes are large, and the implication is that antecedent change could be used to detect ultimate responders. Katz et al (1987Katz et al ( , 1994 estimated effect size at week 1 to vary from .24 to .9 depending on the measure. They used guidelines from Cohen (1988), which suggest that an effect size of .5 is medium and readily detectable to a clinical observer.…”
mentioning
confidence: 99%
“…Because depression is a multi-faceted disorder, some investigators have suggested that any measure used to evaluate early improvement should include subscales measuring cognitive, vegetative, and emotional dimensions [12,27,28]. In this context, Katz and colleagues identified eleven depressive constructs using several rating scales during treatment with imipramine and amitriptyline [23,29].…”
Section: Pharmacological and Non-pharmacological Approaches And Thmentioning
confidence: 99%
“…This issue is particularly critical because several studies have demonstrated the influence of early antidepressant effects in predicting long-term outcome [12,28,31,32]. One study that investigated the time course of improvement in patients randomized to different antidepressants (amitriptyline, oxaprotiline, imipramine, moclobemide) found a significant difference between active drug and placebo after five days of treatment, an effect that continued to increase during the first two weeks [33].…”
Section: Pharmacological and Non-pharmacological Approaches And Thmentioning
confidence: 99%
See 1 more Smart Citation